AN ASSESSMENT OF TERTIARY INSTITUTIONS’ EXAMINATIONS CHALLENGES IN NIGERIA: IMPLICATION FOR DECISION MAKING - Ogunode, Niyi Jacob; Akuh Ph.D , Esther A.; Tadi, Philemon L. (Journal of Learning on History and Social Sciences, 2024)
This paper assessed the challenges militating against conduct of examinations in the tertiary institutions in Nigeria. Relevant journals and conference papers were consulted and are sources of secondary data used in the paper. The paper identified funding problems, inadequate infrastructure facilities, corruption, examination mal-practices, technological facilities, strike actions and insecurity problems as challenges militating against effective conduct of examinations in tertiary institutions in Nigeria. Based on these findings, the paper recommends an increment in the budgetary allocation of tertiary institutions. Provision of modern infrastructure facilities. Deployment and installation of CCTV cameras in all examination halls and theatres. Examination marking should be taken away from lecturers to a special centre where marking of exams scripts will be decentralized. Government should implement all agreement reached with different trade unions to curtain strike actions in the various institutions. Government should address all issues breeding insecurities in Nigeria